حق المستهلك في العدول عن التعاقد الالكتروني دراسة مقارنة - صحراوي، مسعودة (University Of Eloued جامعة الوادي, 2025)
حملت هذه الدراسة مسمى حق المستهلك في العدول، اعتبارا من كونه إحدى الوسائل الحمائية التي أقرها القانون، وأدرجت في التعاقد الالكتروني لتأكيد أهمية ممارسة هذا النوع من الضمانات على العقود التي تبرم عبر وسائل الاتصال الحديثة. وحق العدول رخصة قانونية منحت للمستهلك الالكتروني يستعمله بإرادته المنفردة ذو صفة تقديرية ومجانية يتعلق بالنظام العام يختلف عن الأنظمة المشابه له، يمارسه صاحبه على العقود التي يبرمها عن بعد مع المورد خلال مدة زمنية يحددها القانون حسب محل العقد وطبيعته، يستثنى من دائرة إعماله مجموعة من العقود، وهدف المشرع من وراء تقييد استعمال هذا الحق بمجموعة من الضوابط الحفاظ على مصالح الأطراف المتعاقدة. بالإضافة إلى أن هذا الحق وإن كان يعد خروجا عن القاعدة العامة "العقد شريعة المتعاقدين" ومبدا "القوة الملزمة للعقد"، إلا أن المشرع حاول من وراءه إعادة التوازن إلى العقد والحفاظ على استقرار المعاملات المالية بين الأطراف، الذين تجمعهم علاقة تعاقدية غير متكافئة، تتصف بالضعف المعرفي لأحد أطرافها-المستهلك- في مقابل القوة المعرفية نتيجة المركز الاقتصادي للطرف الأخر-المورد-. Abstract: This study, titled "The Consumer's Right of Withdrawal," examines this right as a protective measure recognized by law and incorporated into electronic contracts. This underscores the importance of exercising such guarantees in agreements concluded through modern communication methods. The right of withdrawal is a legal prerogative granted to the electronic consumer, exercised unilaterally at their discretion and without charge. It relates to public order and differs from similar legal frameworks. The consumer exercises this right in contracts concluded remotely with a supplier, within a timeframe specified by law, depending on the subject matter and nature of the contract. A group of contracts are excluded from its application. The legislator's objective in restricting the exercise of this right with various controls is to preserve the interests of the contracting parties. Furthermore, although this right represents a departure from the general principle of "Pacta sunt servanda" (contracts are binding on the parties) and the principle of the binding force of contracts, the legislator sought to restore balance to the contract and maintain stability in financial transactions between parties. These parties are often in an unequal contractual relationship, characterized by the consumer's informational weakness compared to the supplier's informational strength, which stems from their economic position.
Thesis
Keywords: حق العدول; المستهلك الالكتروني; المورد; العقد الالكتروني; Right of Withdrawal; Electronic Consumer; Supplier; Electronic Contract